CONVERSION OF THE LOW QUALITY INDONESIAN NATURALLY-OCCURRING MINERALS INTO SELECTIVE TYPE OF ZEOLITES BY SEED-ASSISTED SYNTHESIS METHOD - Rino R. Mukti; Shofarul Wustoni; Agus Wahyudi; Ismunandar Ismunandar (Indonesian Journal of Chemistry, 2013)
An X-ray diffraction (XRD) revealed that Indonesian naturally-occurring mineral from Nanggung, Bogor shows to be a low quality product as it does not seem to contain any zeolite materials. As located in the volcanic area, Indonesia essentially has abundant source of natural zeolites and the country has put much efforts on these treasured materials for export commodity. In order to bring the local natural mineral into high value and to discover whether the mineral has at least zeolitic fragments, we have implemented seed-assisted synthesis to see the possibility of growing zeolite and turn this mineral into high quality. In principle, once the mineral has zeolitic fragment or nuclei, recrystallization of the mineral may occur. By utilizing this mineral as seed in aluminosilicate mother solution, selective mordenite-type (MOR) zeolite can be obtained after hydrothermal treatment. Characterization by XRD showed that this MOR zeolite has high crystallinity and scanning electron microscopy (SEM) depicted the crystal morphology. The natural mineral is conclusively essential for the formation of MOR zeolite by seeding the aluminosilicate mother solution. In the absence of aluminosilicate mother solution, natural mineral can be recrystallized into selective analcime-type (ANA) zeolite. MOR zeolite is known to be useful for several applications such as catalysis whereas ANA zeolite has been considered to be less potential due to relatively small microporosity.